Molecular recognition using tetralactam macrocycles with parallel aromatic sidewalls - Li, Dong-Hao; Smith, Bradley D. (Beilstein Journal of Organic Chemistry, 2019)
This review summarizes the supramolecular properties of tetralactam macrocycles that have parallel aromatic sidewalls and four NH residues directed into the macrocyclic cavity. These macrocycles are versatile hosts for a large number of different guest structures in water and organic solvents, and they are well-suited for a range of supramolecular applications. The macrocyclic cavity contains a mixture of polar functional groups and non-polar surfaces which is reminiscent of the amphiphilic binding pockets within many proteins. In water, the aromatic surfaces in the tetralactam cavity drive high affinity due the hydrophobic effect and the NH groups provide secondary interactions that induce binding selectivity. In organic solvents, the supramolecular factors are reversed; the polar NH groups drive high affinity and the aromatic surfaces provide the secondary interactions. In addition to an amphiphilic cavity, macrocyclic tetralactams exhibit conformational flexibility, and the combination of properties enables them to be effective hosts for a wide range of guest molecules including organic biscarbonyl derivatives, near-infrared dyes, acenes, precious metal halide complexes, trimethylammonium ion-pairs, and saccharides.
Keywords: fluorescent dye; host–guest chemistry; hydrogen bonding; hydrophobic effect; macrocycles; rotaxane; supramolecular